Differences in Force-Velocity Profiles During Countermovement Jump and Flywheel Squats and Associations With a Different Change of Direction Tests in Elite Karatekas - Smajla, Darjan; Spudić, Darjan; Kozinc, Žiga; Šarabon, Nejc (Frontiers in Physiology, 2022)
The force-velocity (F-v) relationship has been proposed as a biomechanical characteristic to comprehensively evaluate neuromuscular capabilities within different tasks such as vertical jumping, sprinting and bench pressing. F-v relationship during flywheel (FW) squats was already validated, however, it was never compared to F-v profile of vertical jumps or associated with change of direction (CoD) performance. The aims of our study were (1) to compare F-v profiles measured during counter movement jumps (CMJs) and FW squats, (2) to determine correlations of F-v mechanical capacities with different CoD tests, (3) to investigate the portion of explained variance in CoD tests with the F-v outcome measures. A cross-sectional study was conducted on 39 elite karatekas. They performed CMJs and FW squats using progressive loads to calculate F-v profile outcome variables and different CoD tests (CoD at 90°, CoD at 180°, T-test, short karate specific test (KST) and long KST). Our results showed significantly higher values in all F-v outcome variables (F0 – maximal theoretical foce, v0 – maximal theoretical velocity, Pmax – maximal power output, F-vslope – the slope of F-v relationship) calculated from CMJs compared to FW squats (all p < 0.01). Significant positive moderate correlations between the tasks were found for F0 and Pmax (r = 0.323-0.378, p < 0.05). In comparison to F-v outcomes variables obtained in FW squats, higher correlations were found between F-v outcome variables calculated from CMJs and CoD tests. The only significant correlation in F-v outcome variables calculated from FW squats was found between Pmax and short KST time. For all CoD tests, only one F-v predictor was included; more specifically – CMJ-F0 for CoD 90°, CoD 180° and T-test, and FW-Pmax for short KST performance. To conclude, our results showed that F-v relationship between CMJs and FW squats differed significantly and cannot be used interchangeably for F-v profiling. Moreover, we confirmed that high force and power production is important for the successful performance of general and karate specific CoD tasks.